Analysis of Load Flow and Short Circuit Against the Addition of Distributed Generation (DG) in Distribution Networks - Ridwan, Ahmad; El Gazaly, Aejelina; Tjahjono, Anang (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
This study tries to determine the level of change in short-circuit fault currents on certain buses in the Andalas University distribution network due to the installation of a new generator. Simulation of load flow and short circuit faults uses a 20 kV Andalas University distribution network system model to which a renewable generator with a capacity of 200 kW will be added. The simulation results of the load flow on a 20 kV distribution system paralleled with DG show that the voltage drop is still in accordance with the provisions of PT. PLN, this is due to the voltage drop in the distribution system is not up to 10% of the nominal 20 kV. While the short circuit simulation results, the largest single-phase and three-phase short-circuit current values occur at the Nursing_P location of 9.362 kA. However, the short circuit capacity has not yet reached a maximum voltage of 20 kV 500 MVA or 14.4 kA. So that the amount of short circuit current contributed by Nursing_P is within normal limits and does not require additional equipment to protect the fault current.